Theorizing Social Justice Ambiguities in an Era of Neoliberalism: The Case of Postapartheid South Africa. Issue 6 (December 2013) - Subreenduth, Sharon
Abstract In this essay, Sharon Subreenduth explores how social justice policies have both global–local and historical dynamics and maintains that, as a result, dominant Western models of social justice limit engagement with alternative modes of understanding social justice in non‐Western locations. She uses the South African experience as a case study for examining the complexities of social justice policy in the context of the decolonizing efforts that undergird national policy in South Africa as it simultaneously negotiates neoliberal globalizing dynamics. The essay specifically analyzes the neoliberal concept of choice and how it figures within the discourse and practice of race and education within society. Moving beyond binaries, Subreenduth highlights the murky areas of social justice and articulates what they tell us about meta‐analysis, narrative, resistance, complicities, infiltration, and the neoliberal il/logic of local–global histories.